Pengaruh Pemberian Nata De Nanno dan Nannochloropsis oculata terhadap Populasi Brachionus plicatilis [Effect Of Giving Nata De Nanno and Nannochloropsis oculata on Population Of Brachionus plicatilis] - Laksmi Sulmartiwi; Indah Permata Sari; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract This study aims to determine the effect of Nata De Nanno and Nannochloropsis oculata for Brachionus plicatilis population. The research method used was experimental with a Completely Randomized Design (CRD) with six treatments and four replications. The treatments used were: (A) Nata de Nanno 5x109 cells/L N. oculata, (B) Nata de Nanno 4x109 cells/L N. oculata, (C) Nata de Nanno 3x109 cells/L N. oculata, (D) N. oculata 5x109 cells/L, (E) N. oculata 4x109 cells/L and (F) N. oculata 3x109 cells/L. Analysis of data using variant analysis (ANOVA) and to determine the differences between treatments performed tests Distance Regression Duncan. The results showed that administration of Nata De Nanno and Nannochloropsis oculata for Brachionus plicatilis populations exert a significantly different (p<0,05) in each treatment delivery Nata De Nanno and Nannochloropsis oculata with the highest peak population of young B. plicatilis achieved on the fifth day of treatment D (N. oculata) with a concentration of 5x109 cells/L produce a population young B. plicatilis as much as 98,5 individuals/ml. The lowest peak population of young B. plicatilis on the fifth in treatment C (Nata de Nanno) with a concentration of 3x109 cells/L N. oculata 76,75 produce a population of young B. plicatilis 76,75 individuals/ml. Water quality parameters during the study was the temperature ranges between 27-31°C, a salinity of 31 ppt, pH value 7, DO (Dissolved oxygen) ranged between 5-8 mg/L, and ammonia levels ranged from 0-0.25 mg/L.